2008
DOI: 10.1161/circheartfailure.108.796789
|View full text |Cite
|
Sign up to set email alerts
|

PDE5A Inhibitor Treatment of Persistent Pulmonary Hypertension After Mechanical Circulatory Support

Abstract: BACKGROUND Pulmonary hypertension (PH) secondary to left heart failure portends a poor prognosis and is a relative contraindication to heart transplantation at many centers. We tested the hypothesis that when PH persists after adequate left ventricle (LV) unloading via recent left ventricular assist device (LVAD) therapy, phosphodiesterase type 5A (PDE5A) inhibition would decrease PH in this population. METHODS AND RESULTS We performed an open-label clinical trial using control patients not receiving therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(108 citation statements)
references
References 38 publications
1
107
0
Order By: Relevance
“…25,26 Sildenafil is a phosphodiesterase-5 (PDE-5) inhibitor commonly used as a selective vasodilator and can lower PVR in persistent pulmonary hypertension post-LVAD implant. 27 …”
Section: Pulmonary Vasodilatorsmentioning
confidence: 99%
“…25,26 Sildenafil is a phosphodiesterase-5 (PDE-5) inhibitor commonly used as a selective vasodilator and can lower PVR in persistent pulmonary hypertension post-LVAD implant. 27 …”
Section: Pulmonary Vasodilatorsmentioning
confidence: 99%
“…Although some studies have demonstrated a decrease in PVR after LVAD [7,8,26], the majority of this literature comes from retrospective, single center data that either included patients on pulmonary vasodilator therapy or did not describe whether such therapy was used. There are also data from a prospective study by Tedford et al [9] that indicates some patients with persistent PH after LVAD insertion do not experience a decrease in PVR over time despite LV unloading. Ultimately, it remains unclear whether pulmonary vasodilator therapy provides a significant benefit to patients with elevated PVR and/or RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, many patients will have a persistently elevated PVR despite left-sided mechanical support [9]. Moreover, those with persistent PH and RV dysfunction are at increased risk of adverse complications, including death, following the initiation of LVAD support [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54][55] If pulmonary vascular resistance remains elevated, sildenafil may be considered. 56 Other contraindications to transplant such as severe chronic kidney disease or morbid obesity seldom improve to a degree that allows listing. Given the scarcity of donor organs and improving outcomes with LVAD support, recipients who are not transplant candidates at time of implant should be prepared for the possibility of lifetime mechanical support.…”
Section: Evolving Role For Lvads and Transplantationmentioning
confidence: 99%